REDD+ as a Source of Conflict and Cooperation - Gritten, David; Silori, Chandra; Suzuki, Regan; Dhiaulhaq, Ahmad (Journal of Forest and Livelihood, 2013)
DOI: http://dx.doi.org/10.3126/jfl.v11i2.8625 Journal of Forestry and Livelihood Vol.11(2) 2013 75-81